Plant diversity and vegetation structure across reclamation ages in a tropical gold mine landscape, North Sumatra, Indonesia - SYAIFUL ANWAR; ASYRAF BIN MANSOR; HAZZEMAN HARIS; RIZKY WAHYUDI; QESHY NATA HAYATI; BUDIMAN BUDIMAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Anwar S, Mansor AB, Haris H, Wahyudi R, Hayati QN, Budiman. 2025. Plant diversity and vegetation structure across reclamation ages in a tropical gold mine landscape, North Sumatra, Indonesia. Biodiversitas 26: 6056-6073. Restoration is essential to recover biodiversity in post-mining landscapes. This study aimed to descriptively compare the plant diversity and vegetation structure in reclamation sites aged 3 to 12 years at the Martabe gold mine, North Sumatra, Indonesia. Vegetation was sampled using nested quadrat methods with 10% sampling intensity (2.36 ha of 22.8 ha total area); species richness (S), Shannon–Wiener diversity (H?), Margalef richness (R), and evenness (E) were calculated. The Morisita index quantified community similarity, and species dominance was assessed using the Importance Value Index (IVI). Density profiles (ind·ha-¹) were also constructed to examine stand structure. This research provides novel insights into the trajectories of ecological succession and restoration potential in tropical mining landscapes. Across all age groups, 177 species were recorded, with seedling-stage richness peaking at 58 species in 3-year-old sites. Seedling communities showed high diversity but low evenness, indicating pioneer species dominance. Sapling and pole stages exhibited moderate diversity with balanced species distributions, while tree communities had the lowest richness but increasing evenness with age. Community similarity increased from the seedling to the tree stage, suggesting convergence toward a mature assemblage. Falcataria falcata dominated the tree layer, while Samanea saman and Hibiscus tiliaceus prevailed in sapling and pole layers. Pioneer plants like Melastoma malabathricum and Asystasia gangetica were common among the young seedlings. The vegetation density displayed an inverted J-shaped pattern, indicating healthy regrowth. These findings reveal changes in species composition, dominance, and structure over a decade of reclamation, providing valuable information to enhance mine-land restoration strategies in tropical regions.